PENGARUH PEMBIASAAN TANGGUNG JAWAB TERHADAP KARAKTER KEJUJURAN SISWA KELAS XI SMA NEGERI 12 PEKANBARU - Jenika Dwi Fitria; Hambali; Haryono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted because it was motivated by the lack of honesty character of students in schools, one of the efforts to minimize the problem is the habit of responsibility in schools. The formulation of the problem contained in this study is whether the habit of responsibility affects the honesty character of class XI students of State Senior High School 12 Pekanbaru. This study aims to determine whether the habit of responsibility affects the honesty character of class XI students of State Senior High School 12 Pekanbaru. The benefit of this study is expected to be a school guide to the habit of responsibility and honesty character of students. Then it becomes a reference material regarding the influence of the habit of responsibility on the honesty character of students. The research method used is a quantitative method through the results of the coefficient of determination test analysis obtained that the influence of the habit of responsibility on the honesty character of class XI is 28.7% and the rest is influenced by other factors not examined in this study.